Contestation of Marga Primodialsm in Pakpak Bharat Regency Elections (Study on The Election of The Regent and Vice Regent of Pakpak Bharat Regency in 2020) - Jekki Tumangger; Ibrahim Ibrahim; Ranto Ranto (International Journal of Regional Innovation, 2022)
Primordialism is a view or understanding that holds fast to things that are brought from childhood. Primordialism is one of the factors that often becomes a tool in political battles. Likewise in the Pakpak Bharat Regency area, clan primordialism is an inseparable part of every regional head election. The history of the government of Pakpak Bharat Regency shows the magnitude of the influence of local clans in winning candidates for regional heads. This research was conducted to find out how much influence the clan had in the 2020 Pakpak Bharat district election and how the process of fighting for primoerdialism took place. This study uses a descriptive qualitative approach. The technique used in data collection is by conducting interviews and document data from various agencies. Interviews were conducted to find out how the community's perspective on the influence of the struggle for clan primordialism in the elections of Pakpak Bharat Regency. Then the document data obtained from the agency/institution is supporting data regarding the history, culture and population of the people of Pakpak Bharat Regency. The results of this study describe the clan contestation in the 2020 Pakpak Bharat Regency election and the consequences of this contestation in the life of the Pakpak Bharat Regency community. The position of regional head which has always been won by the Berutu clan for the last 15 years has made its own strength and pride for the Berutu clan, and being the strongest political opponent in the last 10 years was the Tumangger clan and the clan political battle was repeated in 2020 and was won by the Tumangger clan and broke the chain of victories of the Berutu clan for the last 15 years. The contestation of clan primordialism led to clan political wars and reduced harmony between different clan groups.